The effects of icon characteristics on users' perception - Ghayas, S. (2013)
Modern mobile phone application interfaces have potential to support various age group users. Among the different age groups, older adults have been quite slow in adopting mobile phone applications and its interfaces. Limited research work has been carried out to investigate the graphical icons and examine its ease of use for various age group users. This paper presents an experimental study to determine the recognition rates of icons from two sets of users with different age groups i.e. younger adults (20 - 40 years) and older adults (+50 years). Users responded to a set of questions consisting of 40 icons obtained from two different brands of mobile phones. The findings reveal that recognition rates vary depending on how familiar the icons are to the users. The results from this study could be useful to support application developers to develop mobile phone applications interfaces that are more suitable for various age group users. Â© 2013 Springer International Publishing.